Repercussions of COVID-19 Pandemic on prenatal and antenatal care in Bahadarbad block of Dist Haridwar Uttarakhand, India - Bijalwan, Rajeev; Nautiyal, Ruchira; Yadav, Nikku (Indian Journal of Community Health, 2023)
Background: The incidence of maternal morbidity and mortality gets reduced if antenatal care (ANC) is provided since it focuses on providing birth preparedness, good health maintenance measures, and awareness regarding pregnancy complications as well as danger signs. Methodology: The present study was conducted in the selected 10 villages in the Bahadarbad block of Haridwar (Uttarakhand). 479 out of 580 pregnant women (who had visited Antenatal Health Camps), responded to the questionnaire thus, leading to a response rate of 82.8%. Most respondents, i.e. 96% (n=461), were 21–30 years old. Result: Out of 461 pregnant women, only 45% visited Antenatal Health Camps and 58% were found anemic. The study also indicated that of the pregnant women who visited Antenatal Health Camps during this period, more than 72% of women gave their previous birth in less than two years. Only 15% of women obtained complete ANC (4 Visits) during the study period, just half of the previous year’s coverage (31%) for the same duration. The study found that home deliveries increased significantly during the lockdown period. From April to June 2020, the percentage of home deliveries was 41% while from July to December 2020 it was 24%. Conclusion: The study suggested reduced utilization of ANC services during the pandemic and significant factors were women’s age, residence, educational status, repurposing of maternity healthcare services, fear of COVID-19 transmission, and transportation disruptions. Thus, efforts should be taken to enhance maternal health services.